In-vitro carbofuran induced micronucleus formation in human blood lymphocytes - Sharma, R. K.; Rai, D. K.; Sharma, B. (Cellular and Molecular Biology, 2012)
The farmers in general get exposed to different chemicals including pesticides. Many of these compounds are capable of inducing mutations in DNA and lead to several diseases including cancer. Carbofuran is a broad spectrum pesticide and frequently used in agricultural practices in India. In this study we intended to evaluate DNA damage inflicted by pesticide exposure in human blood lymphocytes under in vitro condition. The lymphocytes were exposed to varying concentrations of carbofuran (0-50Î¼M) and analyzed by means of the micronucleus (MN) test. The results obtained showed significant increase in MN frequency after exposure to 5, 10, 25 and 50Î¼M of carbofuran as compared to the control group. The frequencies of MN were observed to be in concentration dependent manner. As we further increase the concentration of carbofuran, we observed significant decrease in the mean percentage of binucleated cells (70-49%) and increase in the number of micronuclei formed per 1000 binucleated cells. Simultaneously, we also observed reduction in Cytokinesis-Block Proliferation index (CBPI) with increase in the carbofuran concentrations. The results indicate that this pesticide may exhibit genotoxic effect at higher concentrations. This study emphasizes the need to reinforce the good practices campaigns in order to enlighten those who work with pesticides and also to make them aware about the importance of using protective measures.